1998
DOI: 10.1016/s0304-3959(97)00176-0
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of ketamine and morphine injections

Abstract: The compatibility of ketamine and morphine mixture was studied. In addition, pH adjustment to minimise local tissue irritation led to no change in stability of the mixture up to pH 5.9. It appears that ketamine and morphine mixtures are stable over a 24 h period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…As for ketamine hydrochloride, the stability and compatibility test of ketamine hydrochloride combined with other drugs in infusion solutions has been widely demonstrated that ketamine hydrochloride is a highly stable drug. It has been reported to be stable with tramadol hydrochloride,25 morphine hydrochloride,2629 hydromorphone,30,31 fentanyl citrate,32 dexamethasone sodium phosphate,33 clonidine hydrochloride,34 midazolam hydrochloride,34 lormetazepam,34 and propofol35 in binary admixtures. Regarding droperidol, the solubility showed strong pH dependence (pKa was 7.64), which is stable in acid solution and may cause drug precipitation or crystallization in alkaline solution.…”
Section: Discussionmentioning
confidence: 99%
“…As for ketamine hydrochloride, the stability and compatibility test of ketamine hydrochloride combined with other drugs in infusion solutions has been widely demonstrated that ketamine hydrochloride is a highly stable drug. It has been reported to be stable with tramadol hydrochloride,25 morphine hydrochloride,2629 hydromorphone,30,31 fentanyl citrate,32 dexamethasone sodium phosphate,33 clonidine hydrochloride,34 midazolam hydrochloride,34 lormetazepam,34 and propofol35 in binary admixtures. Regarding droperidol, the solubility showed strong pH dependence (pKa was 7.64), which is stable in acid solution and may cause drug precipitation or crystallization in alkaline solution.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine hydrochloride was found to be compatible when diluted with water or 0.9% sodium chloride injection, packaging in glass vials, or polypropylene syringes at room temperature [ 34 – 36 ]. The compatibility and stability studies also reported that most of the tested drugs, such as morphine [ 37 40 ], hydromorphone [ 41 , 42 ], fentanyl citrate [ 43 ], and dexamethasone sodium phosphate [ 44 ], were stable and compatible in the presence of ketamine hydrochloride. Unfortunately, no published information is available on the compatibility and stability of butorphanol in combination with ketamine in PCA solution.…”
Section: Discussionmentioning
confidence: 99%